2001
DOI: 10.1521/scpq.16.3.270.19889
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing cross-cultural school psychology competencies.

Abstract: This Delphi study was designed to identify essential cross-cultural competencies for school psychologists. The investigation extends the results of the Rogers and Lopez (in press) Delphi study by using a distinct panel of experts, different instrumentation, and a modified process to identify cross-cultural competencies for school psychologists. The term cross-cultural is defined broadly and refers to racially, ethnically, culturally and linguistically diverse clients from African American, Asian American, Hisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…The multicultural counseling competencies also provided the starting point for the three studies that identified multicultural competencies in school psychology (Gopaul-McNicol, 1997;Lopez & Rogers, 2001;Rogers & Lopez, 2002). Gopaul-McNicol (1997) identified 15 multicultural competencies needed by school psychologists when working CLD students based on her own personal experiences, a review of school psychology and ethnic minority literature, and empirical research.…”
Section: Overview Of Multicultural Competenciesmentioning
confidence: 99%
See 3 more Smart Citations
“…The multicultural counseling competencies also provided the starting point for the three studies that identified multicultural competencies in school psychology (Gopaul-McNicol, 1997;Lopez & Rogers, 2001;Rogers & Lopez, 2002). Gopaul-McNicol (1997) identified 15 multicultural competencies needed by school psychologists when working CLD students based on her own personal experiences, a review of school psychology and ethnic minority literature, and empirical research.…”
Section: Overview Of Multicultural Competenciesmentioning
confidence: 99%
“…Using these broad categories, Lopez and Rogers (2001) and Rogers and Lopez (2002) conceptualized more specific awareness, knowledge, and skill competencies. These two studies utilized the Delphi method to conceptualize and identify cross-cultural school psychology competencies that address the full spectrum of school psychological services.…”
Section: Overview Of Multicultural Competenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should examine professional competence and professional practices using objective measures based on empirically derived cross-cultural competencies. An examination of empirically based cross-cultural competencies that are relevant to school psychology practices are beginning to emerge in the school psychology literature (Lopez & Rogers, 2001;Rogers & Lopez, 2002) and may provide a basis for how to teach and to assess these skills during training.…”
Section: Limitations Of the Studymentioning
confidence: 99%